Saving Water with a Nudge (or Two) : Evidence from Costa Rica on the Effectiveness and Limits of Low-Cost Behavioral Interventions on Water Use - Miranda, Juan Jose; Datta, Saugato; Zoratto, Laura (Published by Oxford University Press on behalf of the World Bank, 2021)
The study uses a randomized controlled trial to test the impact of simple, inexpensive, and nonpersonalized behavioral interventions (or “nudges”) on water consumption in the context of a developing country. A descriptive social norm intervention using neighborhood comparisons reduces average water consumption in the first two postintervention months by 4.9 percent relative to the control group, while a planning postcard intervention reduces consumption by 4.8 percent. A descriptive social norm intervention using a town-level comparison also reduces water consumption by 3.2 percent, but this effect is not statistically significant. Finally, the study's one-time interventions continue to generate statistically significant reductions in water use for up to four months after they are implemented.